Ameliorasi Tanah Sulfat Masam Potensial untuk Budidaya Tanaman Bawang Merah (Allium ascalonicum L.) - Yenni Yenni (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2012)
Yenni, 2012. Amelioration of Potential Sulphidic Soil for Onion Cultivation (Allium ascalonicum L.). JLSO 1(1): 40-49.Lowlands contains sulphidic soil which is potential for crop production, yet acidic and lack of nutrients which inhibits plant growth. This study was aimed to identify the effects of liming of sulphate soil on the growth of Onion (Allium ascalonicum L.). This study was carried out using factorial completely randomized design with six replicates on sulphate soil. The experiments were performed on poly bag (5 kg soil/poly bag/plant in acid sulphate soil. The first factor was soil pH 4,05 (S1) and 5,02 (S2). The second factor was lime dosage(K0), 1 ton/ha (K1), 2 ton/ha (K2), and 3 ton/ha (K3). The plants were harvested after two month. Parameters measured were the growth of onion such as plant height, leaf number, bulb number, root length, fresh weight and dry weight of tuber. Secondary metabolite content of tuber was determined using gas chromatography. Data obtained werewas analyzed using ANOVAs, followed by Duncan Multiple Range Test (DMRT) with 5% significant level. Data analysis revealed that the combination of soil pH and lime dosage has significant effect on growth and yield of onion. Based on GC analysis, two tons/ha liming in sulphate soil gave the highest secondary metabolite contents.